PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH BERBANTUAN VIDEO UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Listiani, Yetti; Ningsih, Kurnia; Panjaitan, Ruqiah Ganda Putri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research was aimed to improve student learning outcomes through the application of a video assisted make a match learning model on respiratory system material in class VIII A of SMP Negeri 3 Pontianak. Subjects in this study were 36 students. The research method used was classroom action research, which was conducted in two cycles in two meetings, each cycle consisting of four stages namely planning, action, observation, and reflection. The instrument used to collect data in the form of observation sheets of learning processes and multiple choice questions. The results showed the implementation of the learning process well in the first cycle reached 96%, then increased to 100% in the second cycle. The percentage of completeness in cycle I was 75% and in cycle II it increased to 88.89%. The average learning outcomes of students in a row from cycle I to cycle II amounted to 80.70 and 85.00. The conclusion of this research is the video-assisted make a match learning model can improve student learning outcomes on respiratory system material in class VIII A of SMP Negeri 3 Pontianak.Keywords: Learning Outcomes, Make a match, video, Respirstory system.